The effect of maturation stage and after-ripening on seed quality in organically- and conventionally-produced pepper (Capsicum annuum L.) seeds - YILDIRIM, Kutay; DEMIR, Ibrahim (Plant Breeding and Seed Science, 2020)
High quality seed production is essential in organic production as well as in conventional production. Fruit maturity can be observed at different times due to the continuous flowering of pepper plant. Consequently, seeds with different maturity are obtained as the fruits are collected during once over-harvesting period. Immature seeds collected in once over-harvest may cause quality losses in the seed lot. Hence, this study was conducted to determine the effect of after-ripening on mature and immature pepper seeds produced in organic and conventional production systems. To see the effect of after-ripening treatment, seeds were harvested in two different periods (immature 45-50 day after anthesis(DAA) and mature 60-65DAA). After-ripening(AR) was performed by keeping the seeds in fruits for 7 days after harvesting the fruits. Effect of production systems and after-ripening on immature and mature pepper seed lots were assessed for four cultivars harvested in 2015 and 2016. After-ripening increased germination (AR:76.3%, C:28% for organic and AR:88%, C:53.8% for conventional), seedling emergence (AR:70.8%, C:44.3% for organic and AR:82.5%, C:53.8% for conventional) percentages and mean weight of 1000 seeds (AR:6.5, C:6.0g for organic and AR:6.5, C:6.2g for conventional) in both production systems of immature seed lots compared to control (C)(P<0.05) but did not have a similar effect on mature ones. Moreover, organically-produced seed lots have the same quality as conventionally-produced seeds. Consequently, obtained results indicate that after-ripening can be used to enhance the quality of immature seeds of pepper cultivars and seeds can be produced organically without any loss of quality.